Information systems for scientific laboratories: a narrative review (Research, Society and Development, 2022)
Data originated from scientific laboratories require appropriate management. In this sense, there are information systems tailored for this type of working environment, ranging from physical notebooks to personalized electronic platforms. Over time, physical annotation instruments have become no longer sufficient to meet the existing demand in more dynamic research environments. In this context, the objective of this work was to present a narrative review on the key elements surrounding the development of efficient information systems applied to scientific laboratories. In this paper, it is emphasized how essential it is to build customized systems that can specifically meet the needs of the user. This paper also exemplifies the contribution of digital information systems towards research in the areas of life and health sciences. For this, the main concepts and principles involved in the development of scientific research information systems are described, which may be used in the planning stage of new platforms.